2021
DOI: 10.1111/apa.15842
|View full text |Cite
|
Sign up to set email alerts
|

Children hospitalised with four common viral diseases showed epidemiological differences but few socio‐economic variations

Abstract: Aim: This study explored the differences in demographic and socio-economic factors between children hospitalised due to four common viral infections.Methods: Demographic data were obtained from Statistics Sweden on >3000 children admitted to Astrid Lindgren Children's Hospital in 2009-2014 with rotavirus, influenza, respiratory syncytial virus (RSV) or chickenpox. We compared demographic and socio-economic factors between case groups using logistic regression with rotavirus cases as reference.Results: There we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…Nevertheless, RSV was found to be the most common virus detected in inpatients (in 10.55% of inpatients), and was identified as the leading virus in outpatients and inpatients aged < 6-month-old, and inpatients aged 6-to 11-month-old and 1-to 2-year-old. RSV was likely to be related to hospitalization in children, consistent with other studies [8,21]. A systematic analysis conducted in 2019 also showed that RSV contributes substantially to the global morbidity and mortality burden in children aged 0-60 months, especially during the first 6 months of life and in low-income and middle-income countries [2].…”
Section: Discussionsupporting
confidence: 83%
“…Nevertheless, RSV was found to be the most common virus detected in inpatients (in 10.55% of inpatients), and was identified as the leading virus in outpatients and inpatients aged < 6-month-old, and inpatients aged 6-to 11-month-old and 1-to 2-year-old. RSV was likely to be related to hospitalization in children, consistent with other studies [8,21]. A systematic analysis conducted in 2019 also showed that RSV contributes substantially to the global morbidity and mortality burden in children aged 0-60 months, especially during the first 6 months of life and in low-income and middle-income countries [2].…”
Section: Discussionsupporting
confidence: 83%